Analyzing Soliton Solutions of the Extended (3 + 1)-Dimensional Sakovich Equation - Alqahtani, Rubayyi T.; Kaplan, Melike (MDPI AG, 2024)
This work focuses on the utilization of the generalized exponential rational function method (GERFM) to analyze wave propagation of the extended (3 + 1)-dimensional Sakovich equation. The demonstrated effectiveness and robustness of the employed method underscore its relevance to a wider spectrum of nonlinear partial differential equations (NPDEs) in physical phenomena. An examination of the physical characteristics of the generated solutions has been conducted through two- and three-dimensional graphical representations.
Keywords: the extended (3 + 1)-dimensional Sakovich equation; partial differential equations; QA1-939; exact solutions; symbolic computation; Mathematics